2018
DOI: 10.4269/ajtmh.17-0070
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of an Orientia tsutsugamushi Gene Encoding a 56-kDa Type-Specific Antigen in Chiggers, Small Mammals, and Patients from the Southwest Region of Korea

Abstract: A phylogenetic analysis of was performed to elucidate its antigenic diversity in chiggers, small mammals, and patients. Between September 2014 and December 2016, a total of 3,816 chiggers were identified within nine species of four genera in the southwest region of Korea: (49.9%; 1,907/3,816), (21.1%; 804/3,816), (12.4%; 474/3,816), (7.2%; 273/3,816), (6.7%; 256/3,816), (1.3%; 50/3,816), (0.8%; 32/3,816), (0.5%; 18/3,816), and (> 0.1%; 2/3,816). Twelve chiggers (11 and one) tested positive for by polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…In a study by Park in 2014-2016 [13,14] conducted in the same region, the O. tsutsugamushi genotype for the 56-kDaTSA gene detected in L. scutellare belonged to the Boryong strain, whereas other genotypes (Karp, Shimokoshi) were identified in 2017. Although there wasonly one unique type, the Shimokoshi strain was identified in L. palpale.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a study by Park in 2014-2016 [13,14] conducted in the same region, the O. tsutsugamushi genotype for the 56-kDaTSA gene detected in L. scutellare belonged to the Boryong strain, whereas other genotypes (Karp, Shimokoshi) were identified in 2017. Although there wasonly one unique type, the Shimokoshi strain was identified in L. palpale.…”
Section: Discussionmentioning
confidence: 98%
“…DNA was extracted from 20 μl of chigger material using a G-spin Total DNA Extraction Kit (iNtRON Biotechnology, Daejeon, Korea). and then analyzed by PCR for the O. tsutsugamushi 56-kDa TSA gene as described previously [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, according to Song (2016) and Choi et al (2019), A. agrarius was the most common species of wild rodent in South Korea, with a proportion of above 80%. In addition, Song (2016), Park et al (2018), Choi et al (2019) showed that the total trapping rate (TR) of wild rodents was 7.6 to 13.6, which was 0.52. This different may be caused by the differences in the environment and geographical conditions of the survey areas.…”
Section: Discussionmentioning
confidence: 98%